COMPARATIVE EVALUATION OF THE POSSIBILITIES OF THE AGGREGATES (Academicia Globe: Inderscience Research, 2021)
One of the most common operations within machine-tractor units is plowing the land. So let’s look at three aggregates to compare aggregates.For comparative assessments of the main technical and economic indicators of machine-tractor units,the maximum (permissible, actual)